Implementation of a shared decision-making training program for clinicians based on the major depressive disorder guidelines in Japan: A multi-center cluster randomized trial - Takaesu, Yoshikazu; Aoki, Yumi; Tomo, Yui; Tsuboi, Takashi; Ishii, Miho; Imamura, Yayoi; Tachimori, Hisateru; Watanabe, Koichiro (Frontiers in Psychiatry, 2022)
Background Although shared treatment decision-making with patients requires attention, it is not widely implemented, particularly in the field of psychiatry. The aim of this study was to assess whether a shared decision-making (SDM) training program for clinicians based on the major depressive disorder (MDD) guidelines improved the perceived involvement of the decision process for patients with MDD. Methods A multi-center cluster-randomized controlled intervention of a clinician training program based on the Japanese MDD guidelines using related decision aids compared to usual care was conducted among 56 clinicians from 23 institutions. A total of 124 patients with MDD were enrolled in this study. The primary outcomes were the scores of the Shared Decision Making-Questionnaire-9 (SDM-Q-9) and Decision Conflict Scale (DCS) after the first visit to the outpatient clinics. The secondary outcomes were patients’ satisfaction, quality of life, trust in clinicians, and depressive symptoms. Additionally, we evaluated all the observed outcomes at the first and third months of follow-up. Results The scores of the SDM-Q-9 in the SDM training program group were significantly higher than those in the control group at the first visit. However, no significant difference in the DCS scores was found between the two groups. There was no intervention effect for secondary outcomes and the outcomes at the first- and third-month follow-up visits. Conclusion The clinician training program based on the Japanese MDD guidelines can be useful for implementation of SDM. Additional research is needed to confirm the efficacy of this SDM training program. Clinical trial registration [https://www.umin.ac.jp/], identifier [UMIN000034397].